Breast-Feeding: Early Influences on Later Health - Goldberg, G.R. (Springer, 2017)
Breast-Feeding: Early Influences on Later Health is a new book which draws together areas of research in early lifel programming of adult health, with a unique focus on the post-natal period in terms of early life programming particularly the extent to which differences in infant feeding practices can lay an indelible imprint on metabolism and behaviour, and hence affect later function and risk of disease. This is an area where there is much less information currently available than there is for fetal programming, and the book raises many new questions and highlights numerous areas where further research is needed (...)